Elevation‐dependent relationships between climate change and grassland vegetation variation across the Qinghai‐Xizang Plateau. (26th June 2014) - Tao, Jian; Zhang, Yangjian; Dong, Jinwei; Fu, Yu; Zhu, Juntao; Zhang, Geli; Jiang, Yanbin; Tian, Li; Zhang, Xianzhou; Zhang, Tao; Xi, Yi
ABSTRACT As one of the most sensitive regions to climate change, the Qinghai‐Xizang Plateau has been widely investigated as one unity for impacts of climate change on alpine grassland. However, previous findings might be confounded by distinct climate sensitivities at different elevations and different regional climates between Qinghai Province and Xizang Province, which lie at the two sides of Tanggula Mountains. In this study, we explored change trends of grassland vegetation, temperature and precipitation in growing season from 1982 to 2011, and elevation‐dependent effects of climate change on grassland vegetation in the two provinces separately. The plateau grassland greenness gained improvement under climate warming and wetting during the past 30 years, especially in Qinghai Province. Temperature increased significantly with a warming magnitude of more than 1.5 °C over the plateau grassland. The interannual change of precipitation showed contrary trends between the two provinces. The main climate factor driving the grassland vegetation variation varied between the two provinces, with temperature being the main factor in Qinghai Province and precipitation being the main factor in Xizang Province. In particular, a more significant correlation between climate change and grassland vegetation variation was found at higher elevations, which reveals higher climate sensitivity in higher elevation areas of the plateau.